Some aspects of sustainable land management agricultural land use areas within the territorial communities - Kapinos, N. (Land Management, Cadastre and Land Monitoring, 2017)
Land Fund in Ukraine is experiencing excessive human impact, which is reflected in its performance exceeding the allowable agricultural development and land structure imbalance. The environmental condition of land resources close to critical. Among the largest land area occupied by agricultural land (71% of which - 76% is arable land). Violation environmentally acceptable ratio of arable land, natural grasslands and forests negatively affected the sustainability of agricultural landscapes. Throughout the widespread land degradation processes, among which the most ambitious is the erosion (about 57.5% of the territory), pollution (20% of the territory), flooding (about 12% of the territory).Sustainable (balanced) land is one of the key factors of sustainable nature of territorial entities and may be formed of a priority, taking into account environmental factors. In ecological optimization based on value criteria ekolohostabilizuyuchyh and anthropogenic pressures lands should necessarily provide for withdrawal of intensive land use, which in its modal properties can not ensure sustainability of land use. However, today in Ukraine within the territories of communities no project development to optimize land use on the basis of sustainable development.Accordingly, the purpose of the article was the study of certain aspects of Land Management sustainable development of agricultural land within the territories of local communities.The current structure of the land fund of Ukraine was actually formed in the Soviet period, under the influence of policies of extensive agricultural development. Violation environmentally acceptable ratio of arable land, natural grasslands and forests negatively affected the stability and condition of land, which is confirmed by relevant research. In such circumstances, balancing the land proposed to carry out in two stages - the ecological and economic. In ecological optimization criteria based on land value necessarily should include withdrawal from intensive land use, which in its modal properties can not ensure sustainability of land use.In this respect, proposed to use as a criterion factor environmental sustainability of land use and anthropogenic load factor. Assessing the impact of land in the sustainability area council, which depends on the stability of agricultural development area, and tillage intensity of land, construction work is characterized by a coefficient of environmental sustainability of land use.Proved that the crucial part of the ecological optimization of land use on the territory of local communities is a balanced structure of land on the basis of ecologically appropriate use. It is important that quality indicators improve the structure of agricultural land in the optimization occurs within the environmental feasibility, increases the stability of land use and contributes to sustainable and balanced agrolandscapes territory.Economic optimization based on the requirements of the environmental is the next stage will determine on the basis of performance indicators such structure of land crops, which will be harmonized achieved high performance, yield and profitability management.Keywords: sustainable development, environmental sustainability, economic optimization, ecological optimization, environmental sustainability factor, the factor of human activity.